Prognostic significance of early complete response in patients with locally advanced rectal cancer undergoing preoperative chemoradiotherapy: Multicentric study of Turkish Society for Radiation Oncology Group (TROD) - Kılıç, Diclehan; Sert, Fatma; Bilkay Görken, İlknur; Arıcan Alıcıkuş, Zümre; Aktürk, Nesrin; Kaytan Sağlam, Esra; Kizir, Ahmet; Özkök, Serdar; Yılmaz, Hasan Taylan; Göçen, Füsun; Yalman, Deniz (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To assess the effect of various parameters on the oncologic outcomes, including the time interval between therapy and surgery (S) in locally advanced rectal cancer (LARC) patients receiving preoperative chemoradiotherapy (CRT).Materials and Methods: The data of 914 LARC patients who received preoperative CRT between 1994 and 2015 were collected retrospectively. Patients received 45-50.4 Gy RT with 5FU based chemotherapy (CT). They all underwent radical resection followed by maintenance CT. Clinical and pathologic variables were compared between the pCR and no-pCR groups. Survival was estimated by the Kaplan-Meier method and Cox proportional hazard model was used in multivariate analysis.Results: After median follow-up of 60.5 (range=12-297.6) months, median overall survival (OS) was 58.75 months and disease-free survival (DFS) 53.32 months. pCR was observed in 18.9% of all cases. pCR, lymphovascular invasion and metastatic lymph node ratio (mLNR) were significantly associated with OS and DFS on multivariate analysis. The 5-year OS and DFS rates were better in pCR group (95.3% vs 80.7% for OS, p<0.0001 and 87.4% vs 71% for DFS, p<0.0001). pCR patients with 4-8 weeks interval had lower rates of distant metastasis (9% vs 20%, p=0.01) and any recurrences (13.6% vs 29.6%, p=0.001) than the remaining. Both OS and DFS were better in favor of pCR achieved at 4-8 week interval time (p<0.0001 for each).Conclusion: pCR after preoperative CRT in LARC correlated with better oncologic outcome. The best OS and DFS durations were achieved in patients who experienced pCR after 4-8-weeks interval before surgery.